Progress and challenges in integrated traditional Chinese and western medicine in China from 2002 to 2021 - Zhou, Man-Ci; Fei, Yu-Tong; Lai, Xiao-Zhen; Lan, Jian; Liu, Bo; Wang, Zhi-Wei; Fang, Hai; Liu, Jian-Ping; Rong, Hong-Guo (Frontiers in Pharmacology, 2024)
Objective The World Health Organization advocated for enhanced integration of traditional medicine and complementary medicine into national healthcare systems across all countries. This study aims to explore the progress and challenges in integrated traditional Chinese and western medicine (ITCWM) in China over 20 years using nationwide data. Methods This cross-sectional study examined various facets of ITCWM in China in terms of policies, resources, services, and funding. National policy documents from 2009 onwards were retrieved from official websites of the Chinese government. Data on ITCWM resources, services and subsidies from 2002 to 2021 were extracted from the China Statistical Yearbooks of Chinese Medicine and China Health Statistical Yearbooks. Research fund projects with the ITCWM discipline were collected from the database of National Natural Science Foundation of China. A mixed method of both quantitative and qualitative approaches was employed to present a comprehensive overview of the collected data. Results This study presented five key findings. First, despite the issuance of 17 national policies by the Chinese government since 2009 to promote the development of traditional Chinese medicine (TCM), only three of them were specifically tailored for ITCWM. Second, although the average annual growth rates of ITCWM institutions, beds, and practitioners reached 0.35%, 10.56%, and 10.88% from 2002 to 2021, with more equitable allocation of ITCWM resources, the overall proportion of ITCWM remained below 5% in 2021. Third, progress has been made in ITCWM practices, yet service efficiency requires further enhancement. In 2021, ITCWM hospitals accounted for 2% of outpatient and emergency visits and 1.57% of hospital admissions among all hospitals, and 9.82% of delivered services were preventive healthcare services. Fourth, ITCWM served a crucial role in primary healthcare services, but its service capabilities need improvement. From 2007 to 2021, the average growth rates of ITCWM clinics, outpatient departments, and practitioners in outpatient departments were 13.30%, 2.57%, and 12.14%, respectively, while the proportion within TCM hospitals dropped. Lastly, despite the Chinese government’s emphasis on financial investment and related project funding for ITCWM, it remained lower than that allocated to TCM and western medicine. Conclusion ITCWM played a pivotal role in China’s healthcare system to advance individuals’ health and well-being across the lifespan. In the future, China will provide further support to enhance ITCWM health resources and improve service capability, and the strategic integration of ITCWM into the broader healthcare system will play a crucial role in achieving universal health coverage and the Sustainable Development Goals.